Brazilian dance self-perceived impacts on quality of life of people with Parkinson’s - Delabary, Marcela dos Santos; Loch Sbeghen, Isadora; Teixeira da Silva, Eliamary Cristiane; Guzzo Júnior, Carlos Cristiano Espedito; Nogueira Haas, Aline (Frontiers in Psychology, 2024)
Background: Parkinson's disease (PD) causes several motor and non-motor symptoms, resulting in negative impacts on physical, mental, emotional, and social aspects of people with PD quality of life. Dance has been considered as a potential non-pharmacological intervention to improve people with PD motor and non-motor symptoms, thereby enhancing quality of life. Purpose: To analyse the selfperceive impacts of Brazilian Dance on the quality of life (physical, mental, emotional, and social) of PwPD, both before and during the COVID-19 pandemic. Methods: Fourteen participants from the "Dança & Parkinson" project were included in this qualitative study. Data collection instruments consisted of a profile and personal data sheet; assessment of accessibility to the online dance classes; Telephone Montreal Cognitive Assessment by phone call; and semi-structured interview conducted through ZOOM video call. The participants characterization data were calculated using mean, standard deviation, and percentages with the Excel Program version 2013. Qualitative data was analysed using the Thematic Analysis technique in the Nvivo, version 8.0, qualitative analysis of text, sound, and video program. Results:The participants reported facing various challenges in dealing with PD, which negatively impact their quality of life. However, their resilience, acceptance, and dedication to treatment play an important role in coping with the issues related to the disease. Brazilian dance, both in-person before the COVID-19 pandemic and online during the pandemic, led the participants to perceive improvements in physical, mental, emotional, and social aspects of quality of life.The Brazilian dance appears to have a positive impact on the physical, mental, emotional, and social aspects of the participants' quality of life, both before and during the COVID-19 pandemic.